A cosmogenic nuclide-derived chronology of pre-Last Glacial Cycle glaciations during MIS 8 and MIS 6 in northern Patagonia - T. P. M. Leger; A. S. Hein; Á. Rodés; R. G. Bingham; I. Schimmelpfennig; D. Fabel; P. Tapia (Climate of the Past, 2023)
The precise environmental mechanisms controlling Quaternary glacial cycles remain ambiguous. To address this problem, it is critical to better comprehend the drivers of spatio-temporal variability in ice-sheet evolution by establishing reliable chronologies of former outlet-glacier advances. When spanning multiple glacial cycles, such chronologies have the capacity to contribute to knowledge on the topic of interhemispheric phasing of glaciations and climate events. In southern Argentina, reconstructions of this kind are achievable, as Quaternary expansions of the Patagonian Ice Sheet have emplaced a well-preserved geomorphological record covering several glacial cycles. Moreover, robust ice-sheet reconstructions from Patagonia are powerful barometers of former climate change, as Patagonian glaciers are influenced by the Southern Westerly Winds and the Antarctic Circumpolar Current coupled to them. It is essential to better constrain former shifts in these circulation mechanisms as they may have played a critical role in pacing regional and possibly global Quaternary climate change. Here, we present a new set of cosmogenic 10Be and 26Al exposure ages from pre-Last Glacial Cycle moraine boulder, glaciofluvial outwash cobble, and bedrock samples. This dataset constitutes the first direct chronology dating pre-Last Glacial Maximum (LGM) glacier advances in northern Patagonia and completes our effort to date the entire preserved moraine record of the Río Corcovado valley system (43∘ S, 71∘ W). We find that the outermost margins of the study site depict at least three distinct pre-Last Glacial Cycle stadials occurring around 290–270, 270–245, and 130–150 ka. Combined with the local LGM chronology, we discover that a minimum of four distinct Pleistocene stadials occurred during Marine Isotope Stages 8, 6, and 2 in northern Patagonia. Evidence for Marine Isotope Stage 4 and 3 deposits were not found at the study site. This may illustrate former longitudinal and latitudinal asynchronies in the Patagonian Ice Sheet mass balance during these Marine Isotope Stages. We find that the most extensive middle-to-late Pleistocene expansions of the Patagonian Ice Sheet appear to be out of phase with local summer insolation intensity but synchronous with orbitally controlled periods of longer and colder winters. Our findings thus enable the exploration of the potential roles of seasonality and seasonal duration in driving the southern mid-latitude ice-sheet mass balance, and they facilitate novel glacio-geomorphological interpretations for the study region. They also provide empirical constraints on former ice-sheet extent and dynamics that are essential for calibrating numerical ice-sheet and glacial isostatic adjustment models.